Analisis Pengaruh Bauran Pemasaran terhadap Kualitas Jasa dan Kepuasan Pelanggan Eksternal Perguruan Tinggi Swasta di Kota Medan - Sembiring, Beby Karina Fawzeea (Universitas Brawijaya, Indonesia, 2009)
Recently in this free market era, there have been widely open chances for foreign private university to go along with national education exertions. As a result, local private university must enhances it service quality programs such as using marketing-mix concept as an attempt to survive in more hypercompetitive competition. This research aims to verify the correlation between marketing-mix dimensions such as: product, place, promotion, process, people, price and physical evidence with service quality and external customer satisfaction of private university in Medan.Empirical testing Using Structural Equation Modeling (SEM) which is supported by the research hypothesis. The research result indicates that the application of marketing-mix dimensions (7P) can directly affects the improvement of service quality and gives the external customer satisfaction. According to the result, private university must improve its employee performance first.Keywords: Marketing Mix, Service Quality, External Customer Satisfaction.